Review-Measurement and Analysis of Cancer Biomarkers Based on Electrochemical Biosensors - Cui, Feiyun; Zhou, Zhiru; Zhou, H. Susan (Journal of the Electrochemical Society, 2019)
Cancer is a dreadful disease with a high mortality rate, and it has become more and more prevalent worldwide. Early diagnosis, prognosis and treatment monitoring with robust and non-invasive tools will potentially be the future focus. Electrochemical biosensor can be a strong candidate for cancer theranostics owing to their advantage of ultra-sensitivity, high selectivity, low cost, quick readout, and simplicity. Furthermore, electrochemical biosensors are easier to be miniaturized and mass fabricated, which grant them a better fit for point-of-care applications. In this review, various electrochemical measurement methods, bioreceptor surface, signal generation and amplification, integration of electrochemical sensors in microfluidic chips were summarized. Especially, multiplexed and ratiometric electrochemical biosensor were emphasized in cancer biomarkers detection. Then, measurement and analysis of cancers based on electrochemical biosensors in molecular level (DNA, RNA, and protein), organelle level (exosomes), cell level (cell counting, phenotypic and metabolism analysis, drug sensitivity monitoring) were comprehensively discussed. As a new research trend, the integration of electrochemical biosensors in cancer-on-a-chip has been highlighted. In brief, we present an overall review of current advances in cancers measurement and analysis using electrochemical biosensors. Finally, the current challenges and future directions were discussed.